Lower Ordovician conodonts from Washington Land, western North Greenland. - STOUGE S.; BAGNOLI, GABRIELLA; ALBANI, ROBERTO (1985)
Early Canadian (Lower Ordovician) conodonts have been recorded from loose slabs which were collected in 1941 at Kap Clay, Washington Land, western North Greenland. The conodont fauna correlates with Fauna C of the North American Midcontinental Faunal succession and with the Cordylodus angulatus Zone of the Balto-Scanic succession. The conodont fauna is described applying multielement taxonomy.